Determinant of The Poverty in The Moslem Countries: Ibn Khaldun Development Model - Dian Paisal Putra; Indra Indra (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2016)
This current paper examined the determinant of the poverty in the OIC countries. Our empirical model was based on Ibn Khaldun development model that emphasizes several aspects, namely: the country's wealth (proxied by GDP per capita), the role of government (proxied by health and education expenditures), human resources (proxied by HDI), sharia (proxied by corruption perception index), development (proxied by investment), and justice (proxied by Gini index). We used panel data model consisting nine OIC countries over 2003-2012. This study verified that GDP per capita significantly contribute to the reduction of poverty in the OIC countries. We also found that unemployment (as a control variable) encountered a role in triggering poverty in OIC countries. Meanwhile, it found that education expenditure, Gini index, HDI, and Corruption Perception Index found no significant effect on poverty. DOI: 10.15408/sjie.v5i1.3130